Climatic and edaphic influences on productivity and carbon sequestration of farm grown teak (Tectona grandis, linn.f) in Tamil Nadu, India - Krishnan, NS; Anjali, KS; Manimaran, V; Swathiga, G; Hari Prasath, CN; Sivakumar, B; Ravi, R; Sivaprakash, M; Balasubramanian, A (Plant Science Today, 2025)
Teak (Tectona grandis, Linn.f) is one of the most sought-after tree crops due to the exceptional quality and high market value of its timber. Currently, the Indian subcontinent imports a significant quantity of teak to meet its growing demand. The growth and wood quality of teak are influenced by edaphic and climatic variations across sites, a factor that has been largely underexplored in research. The primary objective of the study is to analyse teak growth, wood quality, and carbon sequestration potential under farmland condition. To address this, the study was conducted across three agroclimatic zones of Tamil Nadu: North Eastern Zone (NEZ), North Western Zone (NWZ), and Cauvery Delta Zone (CDZ), focusing specifically on farmland conditions. The analysis encompassed biometric attributes, volume, and carbon sequestration potential of farm-grown teak across different age classes. The findings of the study reveal that among the three agroclimatic zones, the NEZ (15-20 years age class) recorded the highest biometric attributes, including mid diameter (MD) (0.193 m), volume (0.379 m3), heartwood proportion (0.239 m3), and carbon sequestration (0.683 Mg/acre).. Based on the overall performance, trees in the 15-20 years age class exhibited superior heartwood formation under farmland conditions. Therefore, this age class is recommended for teak cultivation in farmland conditions across Tamil Nadu to maximize growth, wood quality, and carbon sequestration potential.